INTEGRASI KURIKULUM BAHASA ARAB PESANTREN TRADISIONAL DAN MODERN DI MADRASAH ALIYAH PROGRAM KEAGAMAAN - Habibi, Burhan Yusuf (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
This study aimed to reveal the integrative Arabic language curriculum development of traditional and modern pesantren in MAPK MAN 1 Surakarta. This study used a qualitative method with case study approach. The subjects of the study consisted of the vice principal of religious program, the dormitory leader, and the Arabic language teachers. The data collection used interviews, observation, and documents analysis. The data analysis used Miles-Huberman interactive analysis which consists of data reduction, data presentation, and conclusion drawing. The results showed that the development of the Arabic language curriculum in MAPK integrated three Arabic language learning programs, namely the morning school Arabic language curriculum, the evening Arabic language tutorials curriculum and the Arabic language curriculum in dormitory or pesantren. The integration of the Arabic language curriculum of traditional and modern pesantren was in the curriculum organizational components, objectives, materials and textbooks, learning methods, and curriculum evaluation developed.